2019
DOI: 10.1371/journal.pone.0223048
|View full text |Cite
|
Sign up to set email alerts
|

Anger while driving in Mexico City

Abstract: This study aims to analyze the level of anger developed by drivers in Mexico City and also understand the behavior that those drivers use to express that anger, using four different survey methods. The first focuses on personal information, the second Driving Anger Expression Inventory (DAX), the third refers to a shorten version of Driving Anger Scale (DAS) and the fourth being the Dula Dangerous Driving Index (DDDI). These have previously been applied and validated in several different countries. The questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 68 publications
3
5
0
2
Order By: Relevance
“…In comparison with driving anger across samples of drivers from various countries, the overall DAS score among Lebanese drivers was 107.5 which is considered high. Our ndings are comparable to the United States where the average score of DAS was 109.0 [52]. However, the average score for the complete DAS was only 69.2 among Japanese drivers [34].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In comparison with driving anger across samples of drivers from various countries, the overall DAS score among Lebanese drivers was 107.5 which is considered high. Our ndings are comparable to the United States where the average score of DAS was 109.0 [52]. However, the average score for the complete DAS was only 69.2 among Japanese drivers [34].…”
Section: Discussionsupporting
confidence: 73%
“…Our ndings showed that Lebanese drivers get angry the most when exposed to hostile gestures. Remarkably, Lebanon ranked the top along with Americans and Turkish, in terms of anger related to hostile gestures (3.79), tra c obstruction (3.39), and illegal driving (3.62) compared to other countries [21,32,33,52]. However, the discourtesy subscale was signi cantly lower among Lebanese drivers compared to American [21], New Zealand [28], German [53], Chinese [33], and Turkish [32] drivers, but this level was similar to the one reported by Spanish drivers [54].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the DDDI as an instrument to measure 3 main domains was found to be worthwhile in such a context, where NCED, AD, and RD needed to be tested elsewhere. [21] Although the period since the legal liberation of female driving in the country has been brief (3 years), our ndings in this study showed that adherence to good-quality driving is less likely for female drivers. Moreover, based on the method used (the DDDI), aggressive, dangerous driving behavior was found to be common among female drivers in Riyadh City, which is similar to ndings from a study done in Mexico.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, based on the method used (the DDDI), aggressive, dangerous driving behavior was found to be common among female drivers in Riyadh City, which is similar to ndings from a study done in Mexico. [21]. However, some authors have attributed the occurrence of accidents with aggressive and speedy driving, but this has not been correlated with drivers' attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) build regional planning models that integrate land use simulation, travel demand modeling, and traffic assignment. Hernández‐Hernández, Siqueiros‐García, Robles‐Belmont, and Gershenson (2019) calculate commute routes and trip distances in a study of motorists’ emotions and expressions of anger in Mexico City. Boeing (2019a) compares driving and walking route circuity by simulating millions of trips across 40 city street networks.…”
Section: Empirical Street Network Science With Osmnxmentioning
confidence: 99%